IMPLEMENTASI PENDIDIKAN POLITIK BERBASIS NILAI-NILAI PANCASILA DI DESA BOBISINGO, GALELA UTARA - Sergie, Misrina; Kamisi, Mohtar; Bulele, Fahmi (Universitas Khairun, 2024)
The results of the research show that politics is basically a phenomenon that is closely related to humans and human actions themselves, which by nature always live together with each other. Humans are social creatures, dynamic and developing and able to adapt to the environment or surrounding circumstances. As members of society, we are of course bound by the general values and rules that are recognized and acknowledged by the community itself. Therefore, politics will always manifest and manifest itself within the framework of the process of human development, with the interrelation of things above humans and of course the essence of political practice itself, whatever the reasons and observations or political analysis, cannot simply leave humans alone. This shows that the essence of politics is human behavior, whether in the form of activities aimed at influencing or maintaining a social order of life by using their respective powers.